Erectile function post robotic radical prostatectomy: technical tips to improve outcomes?. Issue 3 (September 2016) - Goonewardene, S.; Persad, R.; Gillatt, D.
Abstract Robotic surgery is becoming more and more commonplace. At the same time, so are complications, especially related to erectile function. The population being diagnosed with cancer is younger, with more aggressive cancers and higher expectations for good erectile function postoperatively. We conduct a retrospective analysis of literature over 20 years for Embase and Medline. Search terms used include (Robotic) AND (prostatectomy) AND (erectile function). There are a variety of multifactorial causes, resulting in worsening ED post-robotic radical prostatectomy; however, there are a number of treatments that can support this. There is much we can do to help prevent patients getting postoperative erectile dysfunction post-radical surgery. However, part of this is management of realistic patient expectations.